109OPTICAL SYSTEM DESIGN FOR HUMAN EYEUSING GENETIC ALGORITHM - Khorsheed, Suha; Altaei, Mohammed (Iraqi Journal of Science, 2024)
In this paper, an accurate optical system for human eye is designed using new approach based on the genetic algorithm (GA). The eye is assumed consists of two optical elements: cornea and eyelens, the remaining contents are just a supplements for these optical elements. The optimal eye design is obtained by GA with some restrictions related to the determination of the generic structure of the eye. The resulted eye is then tested by comparing its optical functions; once with that of the perfect eye, and another with that in literatures. As a results, the genetic eye was identified the characteristics of the real-life eye, which ensure the efficiency of the evolutionary methods to achieve an intended optical design.